Study of 8/12 flux reversal machine as an alternator - Kushwaha D.; Dwivedi A.; Reddy R.; Srivastava R.K. (My University, 2025)
Flux Reversal Machine (FRM), an emerging doubly salient PM motor is well known for retaining advantage of switched reluctance and PM machine. The paper presents study of a Flux Reversal PM machine as an alternator. Analysis, construction, and experimental results for a 8/12 prototype FRM as a single-phase flux reversal alternator are presented. © 2014 IEEE.